STABILITY OF THE ESTIMITATION OF FREQUENCY OF THE HARMONIOUS SIGNAL WITH THE CONSTANT COMPONENT TO PULSE HINDRANCES - Омельчук, І. (Science-based technologies, 2012)
The impulse interference impact on robustness of quazioptimal frequency estimation of harmonic signal with additive constant component and Gaussian noise are researched. The critical conditions for instability are defined. The dependencies of frequency estimation precision on parameters chaotic impulse interferences are obtained by statistic modeling.